The night watchman : a novel - Erdrich, Louise (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
It is 1953. Thomas Wazhushk is the night watchman at the first factory to open near the Turtle Mountain Reservation in rural North Dakota. He is also a prominent Chippewa Council member, trying to understand a new bill that is soon to be put before Congress. The US Government calls it an 'emancipation' bill; but it isn't about freedom - it threatens the rights of Native Americans to their land, their very identity. How can he fight this betrayal? Unlike most of the girls on the reservation, Pixie - 'Patrice' - Paranteau has no desire to wear herself down on a husband and kids. She works at the factory, earning barely enough to support her mother and brother, let alone her alcoholic father who sometimes returns home to bully her for money. But Patrice needs every penny to get if she's ever going to get to Minnesota to find her missing sister Vera. --
Keywords: Indians of North America -- North Dakota -- Fiction; Ojibwa Indians -- Fiction; Indians termination policy -- Fiction; Watchmen -- Fiction; Cultural Heritage -- Fiction; Indians of North America -- Government relations -- Fiction; Indian termination policy -- Fiction; Dysfunctional families -- Fiction; Missing persons -- Fiction; Turtle Mountain Indian Reservation (N.D.) -- Fiction; North Dakota -- Fiction; Turtle Mountain Band of Chippewa Indians of North Dakota -- Officials and employees -- Fiction; Historical fiction